Eficacia de la consulta previa en el trámite de licencias ambientales en el departamento del Chocó 2006-2011. (2014)
The Department of Chocó is a “territory with an incalculable natural, ethnic and cultural wealth” (¿Qué es él Chocó Biogeográfico?, 2013); Prior consultation is a right and a mechanism involving ethnic groups, however, is not effective, or is an appropriate means to protect the constitutional rights of black communities in the process of environmental licensing in Chocó, because there is no appropriate procedure to ensure the effective participation of speakers. A descriptive study where the analytical method used was performed. It was proved that the decisions of the communities are not binding upon execution of environmental licenses, the lack of regulation generates abuse authorities in the procedural steps.